If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 6y = -24 Solving 2x + 6y = -24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 2x + 6y + -6y = -24 + -6y Combine like terms: 6y + -6y = 0 2x + 0 = -24 + -6y 2x = -24 + -6y Divide each side by '2'. x = -12 + -3y Simplifying x = -12 + -3y
| 17.50b+35r=9817.50 | | f(4)=4x | | -7x-3y=42 | | f(4)=2x | | r=3+2b | | 9+7b=8b-7 | | 3(5y+6)-15y=18 | | 6x(2x-1)-7x=5x-1 | | 2(x+5)-8=92 | | -x+3y=27 | | 7x+12=4x+30 | | 5x+28(x-2)=241 | | 2x^2+x-3=0 | | 5x-y=45 | | 5x-28(x-2)=241 | | 7x+42=4x+90 | | 3x+4y=12 | | X^2+2x+10=0 | | 3n+4n=n+16 | | 6a+2b=3.268 | | x^2-1=8 | | 4x-8=7x+3 | | x-2y=6 | | X^2=6x-1 | | x-77851=94103 | | 2x+2y=-10 | | -4(-3-2z)=9z | | 7x+45=2x+115 | | 25y=4(6y-5) | | 8y=7(y+4) | | 3h+9=3(3+h) | | 5(2x-4)=11x |